Gwinea - państwo po juncie - Zobeniak, Marta (Wydawnictwo Naukowe WNPiD UAM, Poznań, 2012)
After decades of inefficient governance and misuse of authority, the Guinean armed forces are a potential source of instability which could still throw the state (and the region) into chaos. If not reformed thoroughly, they will continue to pose a threat to a democratic civilian rule. The establishment of a transitional government and the ongoing electoral process are a significant opportunity. The objective of the reform process is to establish a much smaller force, accountable to civilians and capable of meeting the country’s security needs. The suspension of the second round of the presidential elections has heightened tension. Fears remained that if the election is not completed successfully, it may seize the opportunity to intervene again. This would be a major setback to any prospect of medium-term reform, which requires respect for civilian rule and oversight.
Guinea - a Country After Junta
Keywords: Gwinea; Junta